UNDERSTANDING HUMAN COMPETENCE AT WORK: AN INTERPRETATIVE APPROACH. - Sandberg, J. (Academy of Management Journal, 2000)
In the prevalent rationalistic approaches, human competence at work is seen as constituted by a specific set of attributes, such as the knowledge and skills used in performing particular work. As a...